Dopamine receptor genetic polymorphisms and body composition in undernourished pastoralists: An exploration of nutrition indices among nomadic and recently settled Ariaal men of northern Kenya - Gray Peter B; Campbell Benjamin; Eisenberg Dan TA; Sorenson Michael D (BMC Evolutionary Biology, 2008)
Abstract Background Minor alleles of the human dopamine receptor polymorphisms, DRD2/TaqI A and DRD4/48 bp, are related to decreased functioning and/or numbers of their respective receptors and have been shown to be correlated with body mass, height and food craving. In addition, the 7R minor allele of the DRD4 gene is at a higher frequency in nomadic compared to sedentary populations. Here we examine polymorphisms in the DRD2 and DRD4 genes with respect to body mass index (BMI) and height among men in two populations of Ariaal pastoralists, one recently settled (n = 87) and the other still nomadic (n = 65). The Ariaal live in northern Kenya, are chronically undernourished and are divided socially among age-sets. Results Frequencies of the DRD4/7R and DRD2/A1 alleles were 19.4% and 28.2%, respectively and did not differ between the nomadic and settled populations. BMI was higher in those with one or two DRD4/7R alleles in the nomadic population, but lower among the settled. Post-hoc analysis suggests that the DRD4 differences in BMI were due primarily to differences in fat free body mass. Height was unrelated to either DRD2/TaqI A or DRD4/48 bp genotypes. Conclusion Our results indicate that the DRD4/7R allele may be more advantageous among nomadic than settled Ariaal men. This result suggests that a selective advantage mediated through behaviour may be responsible for the higher frequency of the 7R alleles in nomadic relative to sedentary populations around the world. In contrast to previous work, we did not find an association between DRD2 genotypes and height. Our results support the idea that human phenotypic expression of genotypes should be rigorously evaluated in diverse environments and genetic backgrounds.